Early detection of Bactrocera zonata infestation in peach fruit using remote sensing technique and application of nematodes for its control - Noura H. Heikal; Magda H. Rady; Bouthaina A. Merdan; Talal S. El-Abbassi; Mervat A. El-Genaidy; Ahmed M. Azazy; Mona S. Yones; Eman E. Essa (Kuwait Journal of Science)
Early detection and monitoring of the internal aspects of Bactrocera zonata infestation in fruits and vegetables are important for sustainable agriculture. The present study depends on the non-destructive detection of B. zonata damage in peach fruits using a high-resolution spectroradiometer to characterize the spectral reflectance pattern of peach fruits in healthy and infested fruits with different pest stages, including egg stage and larval instars. Additionally, five vegetation indices were used to detect infestation. Laboratory trials were carried out to investigate the entomopathogenic nematodes (EPNs) pathogenicity, gamma-irradiated and unirradiated Steinernema carpocapsae, and Heterorhabditis bacteriophora against B. zonata larvae and pupae. The spectral reflectance pattern of healthy peach fruit samples was higher than that of all infested samples. The peak level of light reflection for a peach fruit in a healthy state was observed at 750 nm. Conversely, at 1050 nm, the reflectance was low, and it reached its minimum level at 2150 nm for infested peach fruit. Green spectral zones achieved the highest level of discrimination between healthy and infested peach fruit. There was no noticeable distinction between the blue and SWIR-1 zones. However, SWIR-2, red, and NIR spectral zones exhibited a significant difference as they could differentiate between healthy and infested peach fruit. The normalized pigment chlorophyll index (NPCI) was the best plant index employed in pest identification. As the concentration of EPNs increased, the proportion of mortality additionally increased. Furthermore, this study revealed that irradiation of S. carpocapsae juveniles boosted their pathogenicity toward larvae. The LC50 value decreased from 569.39 infective juveniles (IJs)/larva to 433.43 IJs/larva. There was no significant difference in pupae. However, irradiation of H. bacteriophora juveniles negatively impacted larvae, increasing the LC50 value from 1608.04 IJs/larvae to 2295.73 IJs/larvae by 1.4 fold. Additionally, it significantly affected pupae, as it caused the lowest LC50 value of 402.66 IJs/pupae. The results of this study confirmed hyperspectral data's utility in the early prediction of fruit infestation and differentiated between different stages of B. zonata infestation. Similarly, applying irradiation to EPNs significantly impacts the control of B. zonata.